2011
DOI: 10.1002/pola.24601
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of terminally functionalized polyisobutylene derivatives using diazonium salts

Abstract: A new strategy for the synthesis of end‐functionalized polyisobutylene (PIB) oligomers is detailed. Commercially available vinyl‐terminated PIB oligomers were modified to form aniline‐terminated PIB via an aromatic electrophilic substitution reaction. The PIB‐bound aryl amines so formed were then converted into diazonium salts using isopentyl nitrite and an acid in methylene chloride. These salts served as versatile intermediates in synthetic reactions affording azo dye‐containing PIB derivatives and other ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Since there was no visually apparent leaching of 6 into CH 3 CN, we tested this idea by examining how added hydrocarbon polymer cosolvents reduced the leaching of two chromogenic PIB derivatives 7 and 8 that had visible leaching. The first study of the antileaching effect of added hydrocarbon cosolvents used the PIB 2300 bound azo dye 7 10. In a thermomorphic mixture containing 3 g of heptane and 3 g of CH 3 OH, 7 has a small but detectable solubility in CH 3 OH at 25 °C with an absorbance of 0.36 at 492 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Since there was no visually apparent leaching of 6 into CH 3 CN, we tested this idea by examining how added hydrocarbon polymer cosolvents reduced the leaching of two chromogenic PIB derivatives 7 and 8 that had visible leaching. The first study of the antileaching effect of added hydrocarbon cosolvents used the PIB 2300 bound azo dye 7 10. In a thermomorphic mixture containing 3 g of heptane and 3 g of CH 3 OH, 7 has a small but detectable solubility in CH 3 OH at 25 °C with an absorbance of 0.36 at 492 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The first study of the antileaching effect of added hydrocarbon cosolvents used the PIB 2300 bound azo dye 7. [10] In a thermomorphic mixture containing 3 g of heptane and 3 g of CH 3 OH, 7 has a small but detectable solubility in CH 3 OH at 25 8C with an absorbance of 0.36 at 492 nm. Replacing 1 g of the heptane with 1 g of a polypropylene polymer [11] decreased the leaching of 7 by ca.…”
Section: Methodsmentioning
confidence: 99%
“…In the course of other work in our group centered on designing heptane‐soluble catalyst supports, we found that polyisobutylenes (PIB) can be prepared with terminally substituted metallophthalocyanine groups. We found that these thermally stable PIB‐substituted metallophthalocyanines as well as PIB oligomers with terminal azo dyes are both highly soluble in heptane and other alkanes over a temperature range from about −30 °C to 200 °C. These results suggested that these dyes would also be soluble in polyolefin melts.…”
Section: Introductionmentioning
confidence: 98%